Neuroarchitecture-Based Environmental Cues in Daycare: Supporting Procedural Learning through Children’s Daily Routines - Alief Atho'illah; Sarah Cahyadini; Purwanita Setijanti (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
Daycare is often treated as a practical childcare facility, yet for children it is also a repeated everyday environment where routines, objects, and sensory cues are encountered together. From a neuroarchitecture perspective, this repetition matters because the built environment participates in children’s perception, movement, and routine-based learning. This article aims to analyze how environmental cues and daily routines may support procedural learning in early childhood, with particular attention to caregiver mediation. A conceptual qualitative approach was used, supported by field-informed observation, behavioral mapping, interviews with caregivers and parents, visual documentation, and literature synthesis. The analysis indicates that visual cues, such as color zones, symbols, illustrations, lighting, and spatial orientation, may help children recognize activity areas and anticipate routine sequences. Tactile cues, including carpets, floor textures, fabric, wood, sand, toys, and blocks, support exploration, object manipulation, and repeated bodily action. Caregivers mediate these cues by linking them with expected actions through prompts, gestures, demonstrations, and correction. Age-based tendencies also appear in children’s responses, from guided exploration toward more independent routine performance. This article implies that daycare should be understood as a routine-based learning ecology where environmental cues and caregiver mediation jointly support habit formation.